Experimental and DFT explorations of tert-butyl(1-(2-(4-nitrobenzylidene) -hydrazinyl)-1-oxopropan-2yl)-carbamate on CRCA metal in 1M HCl solution - Srilatha Rao (Results in Surfaces and Interfaces, 2021)
The performance of a novel corrosion inhibitor tert-butyl(1-(2-(4-nitrobenzylidene)hydrazinyl)-1-oxopropan-2yl)carbamate (AAD) has been accounted here along with physicochemical characterization studies like Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), 1H NMR and Density function theory (DFT). Additionally, thermodynamic parameters such as weight loss, Langmuir adsorption, and the effect of temperature are investigated and are incorporated to show the enhancement of inhibition effectiveness with increasing dosages of synthesized inhibitor. A decreasing order of corrosion efficiency has been observed at elevated temperatures. Currently, AAD is examined using electrochemical methods including Potentiodynamic polarization (PDP) and Electrochemical impedance spectroscopy (EIS) to see how effective it is in inhibiting corrosion on cold-rolled close-annealed material (CRCA). According to the examination, the corrosion inhibitor showed anodic type of inhibition activity on CRCA metals with high corrosion efficiency.